Iseilema kunhikannanii (Poaceae: Panicoideae), a new species from Rajasthan, India - Chandra Mohan, Kolagani; Mahesh, Y.; Subramanyam, P.; Sharma, Sushant; Prasad, Kothareddy (Phytotaxa, 2020)
Iseilema kunhikannanii (Poaceae), a new species from the Bundi forest division, Rajasthan, India, is described and illustrated. It is similar to Iseilema holei, but differs mainly by having tubercles on both keels and marginal nerves of spatheole, involucral spikelets lanceolate, lower glumes 5-nerved, upper glumes 1-nerved, central pedicel shorter than the involucral spikelets, lower glume deep cleft at apex and glabrous keels.